Effects of Tai Chi and Baduanjin on muscle mass, muscle function, and activities of daily living in individuals with sarcopenia: a systematic review and meta-analysis - Yang, Sen; Chen, Shuwei; Zhang, Yong; Zhou, Zhixiong; Li, Donghai; Zeng, Ping (Frontiers in Public Health, 2025)
ObjectiveThis study aims to systematically evaluate the effects of Tai Chi and Baduanjin on muscle mass, muscle function, and activities of daily living (ADL) in patients with sarcopenia.MethodsWe conducted a comprehensive literature search across both English and Chinese databases, including the Cochrane Library, PubMed, Embase, CNKI, Wanfang, and VIP, for randomized controlled trials (RCTs) examining the effects of Tai Chi and Baduanjin on patients with sarcopenia. The search covered all studies from the inception of the databases through March 28, 2025. We performed a meta-analysis using RevMan 5.3 and Stata 15.1 software.ResultsA total of 11 RCTs involving 738 participants were included in the meta-analysis. The overall risk of bias was assessed as low, with the methodological quality of the studies ranging from moderate to low-moderate. Compared to controls, both Tai Chi and Baduanjin demonstrated positive improvements in grip strength (SMD = 0.97, 95% CI: 0.42 to 1.52, Z = 3.45, p = 0.001), gait speed (WMD = 0.10, 95% CI: 0.02 to 0.19, Z = 2.47, p = 0.013), and muscle strength (WMD = 1.75, 95% CI: 0.59 to 2.91, Z = 2.95, p = 0.003). However, changes in skeletal muscle mass index (WMD = 0.55, 95% CI: −0.54 to 1.65, Z = 0.99, p = 0.323) and ADL (WMD = 11.04, 95% CI: −2.08 to 24.16, Z = 1.65, p = 0.099) were not accompanied by significant changes. The funnel plots appeared largely symmetrical, indicating minimal concern for publication bias across the primary outcomes. Furthermore, Egger’s tests for grip strength (t = 0.41, p = 0.695), gait speed (t = 1.37, p = 0.265), and skeletal muscle mass index (t = 3.16, p = 0.087) showed no significant publication bias.ConclusionBoth Tai Chi and Baduanjin significantly improve muscle strength and function in patients with sarcopenia. However, the improvements observed in ADL did not reach statistical significance.Systematic review registrationhttps://www.crd.york.ac.uk/PROSPERO/view/CRD420251032762, Identifier CRD420251032762.